Assessing of operationalisation of the results based management approach in the Ministry of Transport, Communication and Infrastructural Development in Zimbabwe - Chilunjika, Alouis (International Knowledge Sharing Platform, 2022)
The study investigates the implementation of the Results Based Management (RBM) approach in the Zimbabwean context, using the Ministry of Transport, Communication and Infrastructural Development as the principal case study. While RMB has several components relating to budgeting, personnel performance, e-governance and monitoring and evaluation; this study is restricted to personnel performance system. Research data was collated through documentary and empirical case study reviews. Study findings suggest that notwithstanding concerted effort towards institutionalizing a results-based culture in state institutions, the politics of administration, resistance to change, lack of significant buy-in amongst employees and management to make the approach successful as well as rampant administrative and technical incapacity challenges, have emerged as major setbacks stalling the process to fruition. These findings raise fundamental questions on the extent to which proper and adequate feasibility measures were established before the initiation of the approach. Crafting strategies for the effective implementation of RBM is essential in order to maximize its benefits while minimizing the negative effects in its implementation. Effectiveness in the implementation of RMB critically hinges on the commitment and support of senior management, customizing of RBM processes and materials, implementing sustainable capacity development initiatives, building ownership through participation of stakeholders as well as making conscious organizational change hinging on Research and Development.